Greening Lithuania's growth - Blöchliger, Hansjörg (OECD Publishing, 2021)
This paper provides an overview on Lithuania's environment and environmental policy. Environmental performance has improved since the mid-2000s. Greenhouse gas emissions declined and decoupled from growth over the past decade, yet per capita emissions increased. Transport and energy are the main sources of emissions and pollution, followed by agriculture and industry. There was much improvement in waste management practices, with a significant reduction of landfills. Yet Lithuania has the highest mortality rate from exposure to air pollution in the OECD. Energy efficiency is a concern, particularly in the housing sector. Pricing of environmentally damaging activities is low. Lithuania sets no CO2 tax, has one of the lowest excise duties on motor fuel, petrol and diesel in the OECD, and has one of the largest 'diesel differentials', the gap in the price of diesel versus gasoline. It also provides among the highest subsidies to fossil fuels. In 2020, the country introduced a purchase tax for passenger vehicles which takes into account emissions. Against this background, the country has scope for increasing fossil fuel taxes and removing subsidies, to reach its ambitious environmental and climate management objectives and the net-zero carbon emission target by 2050
Keywords: Economics; Lithuania